ANALISA KEKUATAN AGREGAT KlAS A MATERIAL KABUPATEN SOLOK - Masril Masril (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2019)
In order to realize the goal of development between an area to another region through land transportation, it is very important in the construction of road facilities. In civil construction science, material that can be used as material greatly determines the quality and quantity of the construction.Base construction or foundation layer is very besides as a foundation layer also to bear the burden of vehicles or traffic that passes through the construction of the road, so that material is needed quality.For the implementation of planning for pavement thickness of pavement construction layers, it is necessary to consider all the factors that can affect road construction such as road function, age of plan, traffic, carrying capacity of land, regional factors, surface index (IP), equivalent numbers, average daily traffic, Pavement Thickness Index and Relative strength Coefficient.In making road construction, the material used determines the quality of the road, so in the implementation of road construction it is necessary to carry out laboratory testing, which in the labor test discussed is coarse aggregates originating from Solok Sumatra B arat district, which will later be used for Base Class A on the road. The implementation of the Tests that the authors carried out was the calculation of the aggregate class A class proportion, Aggregate Specific Gravity, Compaction Test of the Base Class A aggregate mixture, Laboratory CBR Testing, and CBR Plan determination.The test results obtained can be a recommendation whether or not the aggregate can be used. Laboratory test results were obtained from the results of the testing of aggregate Class A material derived from solok. Testing the aggregate proportion of base A meets the requirements because it enters the filter 2